Perceived Use of Computer in Extension Activities by the Extension Officials (Indian Journal of Extension Education, 2020)
Continued rapid developments in computer based information technology are probably the biggest factor for the change in extension system. The computer based technologies provide numerous opportunities to obtain a variety of information for successful attainment of the role of extension professionals which largely depend on their operational competency of these computer based Information communication technological equipment. The study conducted with 40 KVK scientists and 174 extension officials from 11 districts covering all the 10 Agro-climatic zones in Odisha during 2019 revealed that computer use increases self-productivity, easy to learn and operate, useful in job performance as it saves time, easy to document data, collect and transfer of information. Extension officials need facilities to use computer, ensuring power supply, training and guidance, other related infrastructural facilities and fund allocation which may bring computer use in extension activities at a higher level. Place of service, communication channels used, education, age and computer devices used had exhibited significant influence in use of the computer.